Legal Aspects of Press Protection in Countries in Conflict According to International Law - Siti Handayani Herdiyanti; Dhea Alfie; Pipit Yuliarpan; Hadi Purnomo (PT FORMOSA CENDEKIA GLOBAL, 2024)
Protection of press freedom in countries experiencing armed conflict is a critical issue to ensure transparent and accurate access to information during a crisis. Although international legal instruments exist, such as the Geneva Conventions and the International Covenant on Civil and Political Rights, their implementation often faces challenges, including physical violence against journalists, restrictions on access to information, and intimidation. This study evaluates the effectiveness of international legal protections and identifies key challenges faced by journalists in the field. In addition, the study makes recommendations for strengthening international law enforcement, support for international organizations, national legal reform, and journalist training. These efforts are expected to improve the protection of press freedom and ensure that critical information remains accessible during times of conflict